Genome-wide association studies with prolapsed gland of the third eyelid in dogs - Zeng, Yu; Feng, Cundong; Jiang, Zheli; Du, Weian; He, Shan; Li, Xingnuan; Fan, Yi; Ouyang, Xiao; Huang, Bixin; Su, Yan; Wang, Siyu; Wei, Rongxing; et al. (Frontiers in Veterinary Science, 2025)
Cherry eye, the common name for the prolapse of the third eyelid gland in dogs, is a widespread ophthalmic disease affecting dogs of various breeds. This condition severely affects the quality of life of affected dogs, and its underlying cause remains unresolved. In this study, 170K SNP microarray data were collected from 653 brachycephalic dogs and 788 brachycephalic and mesocephalic dogs. These two datasets were analyzed separately in genome-wide association studies (GWAS) involving 12 dog breeds affected by cherry eye. The GWAS analysis of 653 short-headed dogs revealed that four SNPs in the CFA3:15627075-15983629 bp region exceeded the genome-level significance threshold. Association analysis of this region also indicated that these four SNPs were strongly associated. Gene annotation showed that the region contained genes such as KIAA0825, FAM172A, and NR2F1, of which NR2F1 was associated with eye development. The results showed that GWAS analysis performed on 788 short- and medium-headed dogs identified five SNPs in the CFA22:15627075-15983629 bp region that exceeded the genome-level significance threshold, and association analysis was performed in this region, which showed that these five SNPs were strongly associated. In addition, 104 annotated genes were identified in both GWAS. To explore the genes involved in cherry eyes, we performed GO functional enrichment analysis. The genes involved in the high pathway were DIO3 and TTC8. In addition, an in-depth analysis revealed 33 genes associated with eye development and diseases. Our study provides new perspectives for further understanding cherry eye in dogs.